x^2 -2x+5=0

Since x1 and x2 are solutions to the equation:

==> x1^2 -2x1 +5 =0.....(1)

and x2^2 -2x^2+5 =0 ....(2)

We will add (1) and (2) :

x1^2 -2x1+5 + x2^2 -2x2 +5 =0

Rearrange:

x1^2+ x2^2 = 2(x1+x2) -10

But according Viete's rule x1+x2 = -b/a = 2

==> x1^2 +x2^2 = 2(2)-10 = -6

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.